Bridging the knowledge gap: educational needs of Iranian women for virtual breast cancer prevention: a qualitative study - Nayereh Naseri; Fariba Taleghani; Maryam Sadat Hashemi; Arash Najimi (BMC, 2024)
Abstract Background Breast cancer prevention is a globally significant and cost-effective public health priority, particularly in low- and middle-income countries. Empowering women through improved health literacy is a key strategy for reducing the disease burden. However, effective educational programs must be tailored to the specific cultural context and needs of the target community. This study explored the educational needs of Iranian women for a virtual breast cancer prevention program. Methods A descriptive qualitative design was used from January to July 2022. Purposive sampling with maximum variation was utilized to recruit a sample of 28 participants. Data collection was conducted through semi-structured interviews. Following the method outlined by Graneheim and Lundman, qualitative content analysis was employed to analyze the interview data. MAXQDA 2020 software was used for data analysis. Components of trustworthiness, including credibility, dependability, confirmability, and transferability, were considered. Results Our findings identified three primary categories: "developing women's scientific, practical, and attitudinal capabilities"; "features of program content"; and "principles of electronic content design". These results offer valuable insights into the educational needs of Iranian women for virtual breast cancer prevention programs. Conclusions To design an effective virtual program, it is crucial to address all three domains: cognitive, emotional, and psychomotor. Program content should be organized and presented using methods that sensitize women to the importance of breast cancer prevention and motivate them to participate. Furthermore, the program's design should be grounded in evidence-based practices and principles of electronic content design, ensuring cultural sensitivity to the needs of Iranian women.